Rulers and Patronage in Late Antique Ravenna - Cirelli, Enrico (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić's 70th birthday, 2020)
During Late Antiquity and the Early Middle Ages, empress Galla Placidia, king Theoderic and later Queen Amalasuntha, imperial officers and rulers, such as Exarchs, bishops and the clergy used patronage of various monumental buildings to endorse their political ambitions, social positions, and prestige, also in Ravenna, when the city became the new Imperial Seat. In this paper I will try to define this phenomenon by showing the role played by private élites since the 4th century, which grew into a general and wide trend by the end of the 8th century, during the Carolingian Age.